2002
DOI: 10.1121/1.1448339
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between low-frequency aircraft noise and annoyance due to rattle and vibration

Abstract: A near-replication of a study of the annoyance of rattle and vibration attributable to aircraft noise [Fidell et al., J. Acoust. Soc. Am. 106, 1408-1415 (1999)] was conducted in the vicinity of Minneapolis-St. Paul International Airport (MSP). The findings of the current study were similar to those reported earlier with respect to the types of objects cited as sources of rattle in homes, frequencies of notice of rattle, and the prevalence of annoyance due to aircraft noise-induced rattle. A reliably lower prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 12 publications
(5 reference statements)
0
10
1
Order By: Relevance
“…Fidell et al, 16,17 Leventhal, 18 and Huang et al 19 all found that the low frequency noise was relatively more important in explaining noise annoyance than in this study. Considering Nakamura and Tokita's low frequency noise threshold curves 20 it appears that the low frequency content in our study was less dominant (subjectively) than the mid and high frequency content, even for the LF boosted conditions.…”
Section: Resultscontrasting
confidence: 55%
“…Fidell et al, 16,17 Leventhal, 18 and Huang et al 19 all found that the low frequency noise was relatively more important in explaining noise annoyance than in this study. Considering Nakamura and Tokita's low frequency noise threshold curves 20 it appears that the low frequency content in our study was less dominant (subjectively) than the mid and high frequency content, even for the LF boosted conditions.…”
Section: Resultscontrasting
confidence: 55%
“…A study by Schomer and Neathammer (1987) suggested that the presence of rattle induced by military helicopters caused an offset of 12 dB in the annoyance response to noise by a factor when there was "little vibration or rattles" and 20 dB when there were "high levels of vibration and rattles." Two related field studies (Fidell et al, 1999(Fidell et al, , 2002 investigated the relationship between low-frequency aircraft noise and annoyance due to rattle and vibration. Although no concrete conclusions were drawn from this study, it was suggested that the relationship between annoyance due to vibration induced rattle and low frequency noise exposure could complement the interpretation of the exposure-response relationships for aircraft noise in situations with low flying aircraft or ground noise from aircraft with high levels of annoyance explained in part by vibration induced rattling of elements such as window frames and household objects such as crockery.…”
Section: Introductionmentioning
confidence: 99%
“…Machines prevalently used in living environments do not frequently generate low-frequency noises at sound pressure levels higher than 70 dB(SPL) [1,6,7]. However, noises generated by large transportation machines such as aircraft, ships, and large trucks often contain low-frequency components at sufficiently high sound pressure levels to induce vibratory sensations [1,8,9]. Additionally, in working environments, many machines can be a source of high-level low-frequency noise that can induce vibratory sensation [1,10,11].…”
Section: Discussionmentioning
confidence: 99%